Sequential interaction of chloride and proton ions with the fast gate steer the voltage‐dependent gating in ClC‐2 chloride channels - Sánchez‐Rodríguez, Jorge E.; De Santiago‐Castillo, José A.; Contreras‐Vite, Juan Antonio; Nieto‐Delgado, Pablo G.; Castro‐Chong, Alejandra; Arreola, Jorge (The Journal of physiology, 2012)
Key points Plasma membrane ClC‐2 chloride channels are widely distributed in our body and are important for vision and fertility. ClC‐2 channels are gated by changes in transmembrane voltage despite of lacking a voltage sensor device. It has been hypothesized that the interaction of an external proton with the gating machinery is responsible for voltage‐dependent gating. Here we used electrophysiological recordings and quantitative analysis under different external proton and internal chloride concentrations and found that the voltage dependence of gating is due to interaction between the passing chloride ion and the permeation pathway, with the external proton stabilizing the open state of the channel. The interaction of either H+ or Cl− ions with the fast gate is the major source of voltage (Vm) dependence in ClC Cl− channels. However, the mechanism by which these ions confer Vm dependence to the ClC‐2 Cl− channel remains unclear. By determining the Vm dependence of normalized conductance (Gnorm(Vm)), an index of open probability, ClC‐2 gating was studied at different [H+]i, [H+]o and [Cl−]i. Changing [H+]i by five orders of magnitude whilst [Cl−]i/[Cl−]o= 140/140 or 10/140 mm slightly shifted Gnorm(Vm) to negative Vm without altering the onset kinetics; however, channel closing was slower at acidic pHi. A similar change in [H+]o with [Cl−]i/[Cl−]o= 140/140 mm enhanced Gnorm in a bell‐shaped manner and shifted Gnorm(Vm) curves to positive Vm. Importantly, Gnorm was >0 with [H+]o= 10−10 m but channel closing was slower when [H+]o or [Cl−]i increased implying that ClC‐2 was opened without protonation and that external H+ and/or internal Cl− ions stabilized the open conformation. The analysis of kinetics and steady‐state properties at different [H+]o and [Cl−]i was carried out using a gating Scheme coupled to Cl− permeation. Unlike previous results showing Vm‐dependent protonation, our analysis revealed that fast gate protonation was Vm and Cl− independent and the equilibrium constant for closed–open transition of unprotonated channels was facilitated by elevated [Cl−]i in a Vm‐dependent manner. Hence a Vm dependence of pore occupancy by Cl− induces a conformational change in unprotonated closed channels, before the pore opens, and the open conformation is stabilized by Cl− occupancy and Vm‐independent protonation.